Effects of Rosa roxburghii & edible fungus fermentation broth on immune response and gut microbiota in immunosuppressed mice - Dechang Xu; Jielun Hu; Yadong Zhong; Yanli Zhang; Wenting Liu; Shaoping Nie; Mingyong Xie (Food Science and Human Wellness)
With the rise of probiotics fermentation in food industry, fermented foods have attracted worldwide attention. In this study, protective effects of Rosa roxburghii & edible fungus fermentation broth (REFB) on immune function and gut health in Cyclophosphamide induced immunosuppressed mice were investigated. Results showed that REFB could improve the immune organ index, and promote the proliferation and differentiation of splenic T lymphocytes. In addition, it attenuated intestinal mucosal damage and improved intestinal cellular immunity. REFB administration also up-regulated the expression of IL-4, INF-γ, TNF-α, T-bet and GATA-3 mRNA in small intestine. Furthermore, administration of REFB modulated gut microbiota composition and increased the relative abundance of beneficial genus, such as Bacteroides. It also increased the production of fecal short-chain fatty acids. These indicate that REFB has the potential to improve immunity, alleviate intestinal injury and regulate gut microbiota in immunosuppressed mice.